Real-world prevalence of hepatitis B virus reactivation in cancer patients in Taiwan. (January 2021) - Chen, Chi-Hua; Hsieh, Hui-Hsia; Wu, Tien-Yuan
Background: Hepatitis B virus carriers who receive systemic cancer chemotherapy have been found to be at a higher risk of hepatitis B virus reactivation. However, lack of standard prophylaxis protocol resulted in life-threatening adverse events. Objective: This retrospective study is to investigate prevalence and chemotherapy drug-induced hepatitis B virus reactivation in all types of cancer patients and establish an institutional clinical practice protocol. Methodology: This retrospective cohort study evaluated the incidence of hepatitis B virus infection, the pre-chemotherapy screening rate of hepatitis B surface antigen (HBsAg), and the severity of hepatitis B virus reactivation of cancer patients receiving intravenous chemotherapy between 2013 and 2014. Patients receiving local chemotherapy with intra-cavity instillation, drug- or alcohol-related hepatitis, or chemotherapy for immune diseases were excluded. Results: In total 784 patients, 404 patients (51.53%) underwent hepatitis B virus serum antigen (HBsAg) testing before chemotherapy, and 61 patients (7.78%) tested positive. Only 32 patients (4.08%) received prophylactic hepatitis B virus antiviral therapy. Patients receiving prophylactic antiviral drugs were significantly lower risk of hepatitis B virus reactivation than nonprophylaxis (relative risk, RR: 0.53, number needed to treat, NNT: 12). Moreover, our study found specific single or combined chemotherapy that may cause hepatitis B virus reactivation different from those of other studies conducted in Western countries. The differences may refer to enzymes, proteins and immune response of patients. Conclusions: Our findings indicate that cancer patients receiving prophylactic antiviral drugs remain at risk of hepatitis B virus reactivation during chemotherapy. Therefore, the hepatitis B virus screen and chemotherapy control system was established in 2017 to reduce the risk of hepatitis B virus reactivation and improve patient safety.